Expectations as Determinants of Patient Satisfaction: Concepts, Theory and Evidence - THOMPSON, ANDREW G. H.; SUNOL, ROSA (International journal for quality in health care, 1995)
The apparent lack of conceptual agreement and the inconsistency in the approach to understanding expectations prompted this analysis of the literature in the field of patient satisfaction. A review of 18 journals over the last few years, as well as a number of relevant books, provided the evidence for the state of the current theory. An attempt has been made to distil the main definitions in use, to illustrate practical models of the relationship between expectations and satisfaction, to identify the influential personal and social variables, and to consider the special nature of health care. Some of the empirical methods and findings are then presented, with conclusions made about how the theory of expectations may be developed to assist in understanding patient satisfaction.